Recent advances in the understanding of cilia mechanisms and their applications as therapeutic targets - Saito, Masaki; Otsu, Wataru; Miyadera, Keiko; Nishimura, Yuhei (Frontiers in Molecular Biosciences, 2023)
The primary cilium is a single immotile microtubule-based organelle that protrudes into the extracellular space. Malformations and dysfunctions of the cilia have been associated with various forms of syndromic and non-syndromic diseases, termed ciliopathies. The primary cilium is therefore gaining attention due to its potential as a therapeutic target. In this review, we examine ciliary receptors, ciliogenesis, and ciliary trafficking as possible therapeutic targets. We first discuss the mechanisms of selective distribution, signal transduction, and physiological roles of ciliary receptors. Next, pathways that regulate ciliogenesis, specifically the Aurora A kinase, mammalian target of rapamycin, and ubiquitin-proteasome pathways are examined as therapeutic targets to regulate ciliogenesis. Then, in the photoreceptors, the mechanism of ciliary trafficking which takes place at the transition zone involving the ciliary membrane proteins is reviewed. Finally, some of the current therapeutic advancements highlighting the role of large animal models of photoreceptor ciliopathy are discussed.